Utility of St. George’s respiratory questionnaire in predicting clinical recurrence in chronic pulmonary aspergillosis - Bongomin, Felix (Ther Adv Infect Dis, 2021)
BACKGROUND AND AIMS: Patients with chronic pulmonary aspergillosis (CPA) who discontinue antifungal therapy commonly exhibit disease recurrence. We aimed to evaluate the utility of the St. George’s respiratory questionnaire (SGRQ) in predicting the likelihood of clinical recurrence of CPA in patients who come off antifungal therapy. METHODS: This audit included CPA patients for whom antifungal therapy was discontinued for at least 1 month. Comparisons were made between the quality of life scores at the time of discontinuation of treatment and at the time of diagnosis of clinical recurrence. The change in patients’ self-assessment scores was also compared. RESULTS: There were 33 cases and 44 controls. Of the 33 cases, 22 (67%) were males with a mean age of 62 ± 13 years. The median for the symptom component of quality of life (QoL) changed from 78.4 at the time of discontinuation of therapy to 83.1 units at the time of diagnosis of clinical failure (p = 0.043), whereas that of the impact and activity components changed from 62.7 to 59.1 units (p = 0.387) and 85.0 to 85.9 units (p = 0.153), respectively. At 12 months, the symptoms domain of SGRQ was able to discriminate between cases of clinical recurrence and controls [area under the curve (AUC) 0.7, 95% confidence interval (CI): 0.6–0.8, p = 0.009]. The proportion of patients in very poor health status increased from 3/11 (9.1%) to 11/33 (33.3%) (p = 0.046). CONCLUSION: A deteriorating symptoms component of the SGRQ and a worsening of patients’ self-assessment are associated with clinical recurrence. Failure to improve by >8 units in the symptoms domain appear to be a marker of disease recurrence. We propose that the clinical approach to diagnose recurrent CPA would be a combination of clinical history, SGRQ scoring, chest imaging and a workup to exclude other causes of the patients’ symptoms.